Synthesis of artemisinin derived glycoconjugates inspired by click chemistry - Goswami, Lakshmi; Paul, Sayantan; Kotammagari, Tharun K.; Bhattacharya, Asish K. (New Journal of Chemistry, 2019)
Herein we describe the synthesis of artemisinin based glycoconjugates (9a-i) through employing a Cu(i)-catalysed reaction between -propargylated dihydroartemisinin (7a) and azido sugars (8a-i), with moderate to excellent yields. Our synthesized artemisinin based glycoconjugates (9a-i) could prove to be an interesting class of bioactive molecules, suitable for the study of their various biological activities.

Design and synthesis of eugenol/isoeugenol glycoconjugates and other analogues as antifungal agents against Aspergillus fumigatus - Goswami, Lakshmi; Gupta, Lovely; Paul, Sayantan; Vermani, Maansi; Vijayaraghavan, Pooja; Bhattacharya, Asish K. (RSC Medicinal Chemistry, 2022)
Glycoconjugates are biologically significant molecules as they tend to serve a wide range of intra- and extra-cellular processes depending on their size and complexity. The secondary metabolites of the plant Myristica fragrans, eugenol and isoeugenol, have shown antifungal activities (IC50 1900 mu M). Therefore, we envisioned that glycoconjugates based on these two scaffolds could prove to be potent antifungal agents. Triazole-containing compounds have shown prominent activities as antifungal agents. Based on this, we opined that a Cu(i) catalyzed click reaction could serve as the bridging tool between a eugenol/isoeugenol moiety and sugars to synthesize eugenol/isoeugenol based glycoconjugates. In our present work, we have coupled propargylated eugenol/isoeugenol and azido sugar to furnish eugenol/isoeugenol based glycoconjugates. In another approach, we have carried out hydroxylation of the double bond of eugenol and subsequent azidation of a primary alcohol followed by intramolecular coupling reactions leading to various other analogues. All the synthesized compounds were assayed against an opportunistic pathogenic fungus, Aspergillus fumigatus. Among the synthesized compounds, two analogues have exhibited significant antifungal activities with IC50 values of 5.42 and 9.39 mu M, respectively. The study suggested that these two analogues inhibit cell wall-associated melanin hydrophobicity along with the number of conidia. The synthesized compounds were found to be non-cytotoxic to an untransformed cell line.

Design and synthesis of 1,3-diynes as potent antifungal agents against aspergillus fumigatus - Goswami, Lakshmi; Gupta, Lovely; Paul, Sayantan; Vijayaraghavan, Pooja; Bhattacharya, Asish K. (ChemMedChem, 2023)
Eugenol and isoeugenol, secondary metabolites isolated from the plant Myristica fragrans have displayed antifungal activities against Aspergillus fumigatus (IC50 1900 mu M). Compounds having conjugated unsaturation have been of great use as antifungals i. e. amphotericin B, nystatin and terbinafine etc. Hence, in the present study, we have designed and synthesised 1,3-diynes by utilizing Glaser-Hay and Cadiot-Chodkiewicz coupling reactions to furnish possible antifungal agents. Synthesis of 1,6-diphenoxyhexa-2,4-diyne derivatives was achieved by Cu(I) catalysed coupling of propargylated eugenol, isoeugenol, guaiacol, vanillin and dihydrogenated eugenol or eugenol in good to excellent yields. All the synthesized compounds were evaluated against pathogenic fungus A. fumigatus. Among all the synthesized compounds, one of the compounds was found to be exhibiting promising antifungal activity with IC50 value of 7.75 mu M thereby suggesting that this type of scaffold could pave the way for developing new antifungal agents. The most active compound was found to be low cytotoxic when assayed against L-132 cancer cell line. Effect of the most active compound on ergosterol biosynthesis has also been studied. Also, the most active compound exhibited significant anti-biofilm activity although the concentration was found to be higher than its anti-fungal activity. Morphological changes in the biofilm were remarkable under confocal laser scanning microscopy.
Keywords: 1; 3-Diynes; Antifungal agents; Aspergillus fumigatus; Cadiot-Chodkiewicz; Glaser-Hay

Methanesulfonic acid-catalyzed friedel-crafts alkylation: towards sustainable synthesis of arylalkanes from donor-acceptor cyclopropane ketones - Goswami, Lakshmi; Paul, Sayantan; Mamale, Ajay G.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2024)
We present herein Br & oslash;nsted acid-catalyzed Friedel-Crafts alkylation of phenols with Donor-Acceptor cyclopropane ketones. The presence of the 1,4-diphenyl butan-1-one and 1,3-diphenyl propane-1-one motifs in various naturally occurring biologically significant molecules inspired us to pursue the direct synthesis of these structural frameworks. Utilizing methanesulfonic acid (MeSO3H) as a catalyst, we achieved a more environmentally friendly and high-yielding synthesis, owing to its cost-effectiveness, biodegradability, transition-metal and additives free conditions. Furthermore, we have successfully extended our developed methodology to thiophenols, resulting in the production of sulfur-based butan-1-one derivatives in good yields. The presence of 1,4-diphenyl butan-1-one and 1,3-diphenyl propane-1-one motifs in various naturally occurring biologically significant molecules prompted us to develop a Br & oslash;nsted acid-catalyzed Friedel-Crafts alkylation of phenols with Donor-Acceptor cyclopropane. image
Keywords: donor-acceptor cyclopropane; Friedel-Crafts alkylation; methanesulfonic acid; Phenols; thiophenol

Unveiling the cell wall-targeting mechanisms and multifaceted virulence modulation by a eugenol glycoconjugate against aspergillus fumigatus: insights from in vitro and in ovo studies - Gupta, Lovely; Verma, Shalini; Goswami, Lakshmi; Kamboj, Himanshu; Sen, Pooja; Bhattacharya, Asish K.; Vijayaraghavan, Pooja (Journal of Applied Macrobiology, 2024)
Aim The primary objective of this study was to elucidate the putative cell wall-associated targets of compound 6i, a glycoconjugate of eugenol, in Aspergillus fumigatus, while also evaluating its toxicity and assessing histopathologic alterations in the liver, heart, and kidney of compound 6i-treated embryos using an in ovo model.Method To achieve this aim, compound 6i was synthesized, and a series of biochemical assays were performed to determine its impact on the fungal cell wall. Additionally, quantitative real time-PCR and liquid chromatography-mass spectrometry/mass spectrometry analyses were conducted to investigate changes in gene and protein expression profiles associated with melanin biosynthesis, conidiation, siderophore production, transcriptional regulation of beta-glucan biosynthesis, and calcineurin activity in A. fumigatus.Results The experimental findings revealed that compound 6i exhibited notable antifungal activity against A. fumigatus by perturbing cell wall integrity, hindering ergosterol, glucan, and chitin biosynthesis, and inhibiting catalase production. Moreover, relative gene expression and proteomic analyses demonstrated that compound 6i exerted both downregulatory and upregulatory effects on several crucial genes and proteins involved in the aforementioned fungal processes. Furthermore, increased expression of oxidative stress-related proteins was observed in the presence of compound 6i. Notably, the glycoconjugate of eugenol did not elicit cytotoxicity in the liver, heart, and kidney of chick embryos.Conclusion The current investigation elucidated the multifaceted mechanisms by which compound 6i exerts its antifungal effects against A. fumigatus, primarily through targeting cell wall components and signaling pathways. These findings underscore the potential of the eugenol glycoconjugate as a promising antifungal candidate, warranting further exploration and development for combating A. fumigatus infections.
Keywords: Aspergillus fumigatus; cell wall integrity; Eugenol; Glycoconjugate; Transcription regulators; Virulence

Comprehensive in vitro and in silico assessment of eugenol glycoconjugates against azole and amphotericin B resistant Rhizopus spp. - Sen, Pooja; Gupta, Lovely; Chauhan, Aastha; Goswami, Lakshmi; Bhattacharya, Asish K.; Sengupta, Abhishek; Vijayaraghavan, Pooja (Molecular Biology Reports, 2025)
Background Rhizopus spp. is a major cause of mucormycosis, a severe infectious disease with high morbidity and mortality. Treatment is challenging due to rising antifungal resistance. Glycosylation is a crucial technique for enhancing the properties of phenolic compounds like eugenol. The present study aims to examine the antifungal efficacy of eugenol glycoconjugates against azole and amphotericin B-resistant Rhizopus isolates. Methods and results Out of 50 soil samples, 12 isolates belonging to Mucorales were obtained, of which 7 were identified as Rhizopus spp. via 18S ITS sequencing. Antifungal susceptibility testing (AST) revealed that all Rhizopus isolates were resistant to amphotericin B (MIC > 1 mu g/mL). Most isolates also showed resistance towards posaconazole (MIC > 1 mu g/mL) and itraconazole (MIC > 2 mu g/mL). AST of eugenol glycoconjugate (coded 6g) showed efficacy against resistant Rhizopus isolates, with MIC values ranging from 6.25 mu g/mL to 25 mu g/mL. Flow cytometry confirmed its fungicidal activity, correlating with MIC data. Compound 6g significantly reduced conidial germination within 24 h and exhibited no cytotoxicity on A549 lung cancer cells. In-silico analysis revealed a negative binding affinity of compound 6g for the spore coat protein CotH3, which could be a potential antifungal target. Conclusion Compound 6g could be an potential antifungal molecule against resistant Rhizopus spp, which requires further studies.
Keywords: Antifungals; Eugenol; Glycoconjugates; Mucormycosis; Resistance; Virulence